A Prognostic Approach to the Resonance Failure Problem by Triple Sensing Technology - EROL, Salih Seçkin (Archives of Acoustics, 2020)
Within this study, resonance phenomenon, which is one of the crucial problems in mechanical constructions, has been analyzed with respect to oil starvation failure in a ball bearing. A unique test rig is designed, constructed, and placed in a laboratory ambience. A ball bearing on the electrical motor, which is a component of the test rig, has been selected for acquisition of data within triple sensing technology in vibration, acoustic, and electrical consumption through testing conditions. The target of that study is condition monitoring of oil starvation fault and resonance fault for comparison of various predictive maintenance methods. The testing was carried out within the electrical frequency of 40.5 Hz, which actuated the electrical motor in order to identify the rotation speed. According to the analyzed results, oil starvation fault and resonance fault is most accurately inspected by vibration analysis.